Keberhasilan pembasmian kemiskinan melalui agihan zakat bantuan modal perniagaan = Eradicating poverty outcome through business capital aids of zakat distribution - Mohamad Halim, Ainin Sofiya; Ishak, Suraiya; Che Omar, Ahmad Raflis; Tahir, Zurinah; Hamdan, Hamdino (Universiti Kebangsaan Malaysia, 2025)
Zakat is one of the pillars of Islam compulsory to each Muslim who has fulfilled the specific requirements. Zakat distribution has been expanded in the productive form of business capital aids to develop the potential of qualified asnaf from the needy and poor category to enhance their economic level in a sustainable manner. The objective of the study is to identify and describe the form of value added by the Asnaf entrepreneurial programme towards the empowerment of economic potential as well as to measure the economic status of the asnaf entrepreneurs based on the Human Capital Theory. The data collection has been conducted through distribution of questionnaire involving 40 asnaf entrepreneurs selected through the non-probability sampling namely the purposive sampling. The data are analysed descriptively by the central tendency values which are the mean and standard deviation. The study findings show asnaf entrepreneurial programme value added for asnaf economic potential empowerment has occurred in the form of increased entrepreneurial competencies, availability of business resources and product market opportunities. The level of economic status of the asnaf entrepreneurs shows high achievement scores. The findings proved that zakat distribution in the form of asnaf entrepreneurial programme can reduce poverty among asnaf who possess business capabilities in the long run in line with Human Capital Theory.